Uso e Ocupação do Solo no concelho de Lousada: dinâmicas, padrões e futuro provável - Abrantes, Patrícia (2018)
In the Vale do Sousa and on the borderof the Metropolitan Area of Porto (AMP),the municipality of Lousada is a relevantlaboratory to analyse and model thedynamics of land use /cover because ofthe rural and urban-industrial diffusepattern that it exhibits. This paperproposes a geographic diagnosis of thedynamics and land use patterns thatoccurred between 1995 and 2010, anda simulation model that considers aBusiness as usual (BAU) scenario for landuse/cover in 2025. Results show a clearloss of the agricultural area in benefitof artificial surfaces area (i.e. built-upareas) and a slight decrease of theforest and semi-natural environmentsbetween 1995 and 2010. The simulationmodel for 2025 continues these trends.This analysis presents an interestingperspective to support spatial planningdecision-making, particularly in thelight of climate change, sustainabledevelopment and environmentalpreservation issues.